Delayed Onset Cranial Nerve Palsies After Endovascular Coil Embolization of Direct Carotid-Cavernous Fistulas. Issue 2 (June 2018) - Bou Ghannam, Alaa; Subramanian, Prem S.
Abstract : Background: Late recurrence of visual symptoms associated with carotid-cavernous fistula (CCF), including diplopia, is uncommon and raises concern for new or recurrent fistula formation. Methods: We report 2 patients with traumatic CCFs, where cranial nerve paresis resolved after endovascular CCF treatment only to reappear years later. Results: No evidence of recurrent or new fistula formation was found. Both were treated successfully with strabismus surgery. Conclusions: Although the cause of delayed onset diplopia after successful treatment is still unknown, theories include late compression of cranial nerves within the cavernous sinus due to coil mass that can cause chronic ischemia, delayed inflammation due to a thrombophilic nidus created by the coil mass, or injury to the cranial nerves that manifests later due to decompensated strabismus.